DESIGN IN EDUCATIONAL TECHNOLOGY DESIGN THINKING, DESIGN PROCESS, AND THE DESIGN STUDIO AUTHORS: BRAD HOKANSON AND ANDREW GIBBONS EDITORS BOOK REVIEW BY THADHARPHUT LIMAPORNVANITR - Thadharphut Limapornvanitr (International Journal of Industrial Education and Technology, 2025)
This book is the published record of the Association of Educational Communications and Technology (AECT) forum. AECT is a professional association in the area of Educational Technology. The association focus on research of instructional design and business development to enrich teaching and learning within the United States and across the world. The global studies in educational technology and new applications of recent technologies for learning promote academic research on top of the best practices. This sequence report from the 2012 AECT Summer Research Symposium highlights robust research methodologies used to enhance instructional design in educational technology, specifically focusing on the concept of design thinking. Fifteen full-text articles depicted methodology, process and details of instructional design for the impact of instructional technology.
Keywords: Educational Environments and Student Outcomes; Online and Blended Learning; Education and Technology Integration